Primary mesenchymal chondrosarcoma of the kidney with synchronous implant and infiltrating urothelial carcinoma of the ureter - Xu Hua; Shao MuMin; Sun HuiLi; Li ShunMin (BMC, 2012)
Abstract Primary mesenchymal chondrosarcoma of the kidney is rare, and it shows distinct undifferentiated tumor cells and well differentiated cartilagenous components. Also assident infiltrating urothelial carcinoma of the ureter is an extremely rare cancer. We report a case of primary mesenchymal chondrosarcoma occurring in the left kidney with an ipsilateral and distinct distal ureteric implant, and a coexisting infiltrating urothelial carcinoma of the ureter in a 64-year-old man. Histopathological examination and immunohistochemical studuies showed the classic features of mesenchymal chondrosarcoma in kidney, as well as a few infiltrating urothelial in ureter. Multitarget fluorescence in situ hybridization (FISH) suggested that the development of the urothelial carcinoma in the ureter may be triggered or induced by the chondrosarcoma component. The patient died 2 month after left nephro-ureterectomy. This is the first reported case of a primary mesenchymal chondrosarcoma of the kidney with coexisting infiltrating urothelial carcinoma of the ureter. Virtual Slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1522835667751019